Apollo 12 breccia 12013: Impact-induced partial Pb loss in zircon and its implications for lunar geochronology. (1st June 2018) - Thiessen, F.; Nemchin, A.A.; Snape, J.F.; Bellucci, J.J.; Whitehouse, M.J.
Abstract: Apollo 12 breccia 12013 is composed of two portions, one grey in colour, the other black. The grey portion of the breccia consists mainly of felsite thought to have formed during a single crystallisation event, while the black part is characterized by presence of lithic fragments of noritic rocks and individual plagioclase crystals. In this study, U-Pb analyses of Ca-phosphate and zircon grains were conducted in both portions of the breccia. The zircon grains within the grey portion yielded a large range of ages (4154 ± 7 to 4308 ± 6 Ma, 2σ) and show decreasing U and Th concentrations within the younger grains. Moreover, some grains exhibit recrystallisation features and potentially formation of neoblasts. The latter process requires high temperatures above 1600–1700 °C leading to the decomposition of the primary zircon grain and subsequent formation of new zircon occurring as neoblasts. As a result of the high temperatures, the U-Pb system of the remaining original zircon grains was most likely open for Pb diffusion causing partial resetting and the observed range of 207 Pb/ 206 Pb ages. The event that led to the Pb loss in zircon could potentially be dated by the U-Pb system in Ca-phosphates, which have a weighted average 207 Pb/ 206 Pb age across both lithologies of 3924 ± 3 Ma (95% conf.). This age is identical within error to the combined average 207 Pb/ 206 Pb age of 3926 ± 2 Ma that was previously obtained from Ca-phosphates within Apollo 14 breccias, zircon grains in Apollo 12 impact melt breccias, and the lunar meteorite SaU 169. This age was interpreted to date the Imbrium impact. The zircon grains located within the black portion of the breccia yielded a similar range of ages (4123 ± 13 to 4328 ± 14 Ma, 2σ) to those in the grey portion. Given the brecciated nature of this part of the sample, the interpretation of these ages as representing igneous crystallisation or resetting by impact events remains ambiguous since there is no direct link to their source rocks via textural relationships or crystal chemistry. Similarly, the currently available zircon data set for all lunar samples may be distorted by partial Pb loss, resulting in meaningless and misleading age distribution patterns. Therefore, it is crucial to fully understand and recognize the processes and conditions that may lead to partial resetting of the U-Pb system in zircon in order to better constrain the magmatic and impact history of the Moon.